Acute Liver and Renal Failure: A Rare Adverse Effect Exclusive to Intravenous form of Amiodarone - Robin Paudel; Prerna Dogra; Saurav Suman; Saurav Acharya; Jyoti Matta (Case Reports in Critical Care)
Amiodarone is an antiarrhythmic drug which is highly effective against a wide spectrum of ventricular tachyarrhythmias making it irreplaceable in certain group of patients. We report an unusual case of acute liver and renal failure within 24 hours of initiation of intravenous (IV) amiodarone which resolved after stopping the medication. The mechanism of acute liver and renal toxicity is not clearly known but is believed to be secondary to amiodarone induced (relative) hypotension, idiosyncratic reaction to the drug, and toxicity of the vector that carries the medication, polysorbate-80. In this case review, we discuss the hyperacute drug toxicity caused by IV amiodarone being a distinctly different entity compared to the adverse effects shown by oral amiodarone and support the suggestion that oral amiodarone can be safely administered even in patients who manifest acute hepatitis with the IV form.